Association Between Socioeconomic Factors and the COVID-19 Outbreak in the 39 Well-Developed Cities of China - Yiting Lin; Ping Zhong; Ting Chen (Frontiers Media S.A., 2020)
Background: Socioeconomic factors play an indispensable role in the spread of emerging infectious diseases. Few studies have investigated the role of socioeconomic factors in the spread of COVID-19.Methods: The number of COVID-19 cases in the 39 well-developed cities of China was aggregated by searching the publicly available sources. Socioeconomic indicators (e.g., population, population density, gross domestic product, rural-to-urban migrants, urbanization rate, per-person disposable income, and level of health care) in these cities were also aggregated from the Bureau of Statistics. The data referring to travelers from Wuhan were collected from the Baidu Migration database. A multiple stepwise linear regression model was performed to identify the independent risk factors of the number of cases.Results: As of Mar 19, 2020, a total of 5,939 cases were reported in the 39 well-developed cities with almost half of total cases in China outside of Hubei. The number of cases ranged 20-576, and the median number of cases was 93 (IQR 54-180) in these cities. Nine socioeconomic variables including the number of travelers from Wuhan, population, native population, gross domestic product, Per-person GDP, the number of hospitals, the number of rural-to-urban migrants, traffic capacity, and person-disposable income were recognized as potential contributors of the number of cases. Results of multiple linear regression showed a statistically significant association between the number of cases and the number of travelers from Wuhan (t = 6.746, P = 0.000) and the number of rural-to-urban migrants (t = 3.776, P = 0.001) in these cities. However, other seven potential contributors were not associated with the number of cases. Moreover, a well-fitted multiple regression model was built in this study, and a regression equation was as follows: Y = 0.007Xt + 0.200Xm (adjusted R2 = 0.833).Conclusions: Travelers from Wuhan and rural-to-urban migrants were independently associated with the COVID-19 outbreak in the 39 well-developed cities of China. These findings suggested that travelers from an epicenter and rural-to-urban migrants should be paid more attention in the early stage of the COVID-19 outbreak in the well-developed cities.